PERENCANAAN REKLAMASI DI TIMBUNAN MAHAYUNG PT.BUKIT ASAM (PERSERO) TBK, TANJUNG ENIM, SUMATERA SELATAN - Afriyanti Puspita Sari; Yunasril Yunasril; Syamsul Bahri (Departemen Teknik Pertambangan FT UNP, 2015)
Mining activities conducted in PTBA is directed to undertake the mining environmentally.Mining activities conducted include exploration, land clearing, stripping topsoil, excavation ofoverburden ,coal mining, transporting, processing and marketing of coal. Reclamation is theactivities that are performed throughout the stages of the mining effort to organize, restore, andimprove the quality of the environment and the ecosystem to function returns appropriateallocation. The success of reclamation activities according to Regulations the Minister ofMineral Resources number 07 2014 covering the activities of the arrangement of land, thepromised land of tops (top soil), water management and erosion control, revegetation and theprevention and mitigation of acid mine water. All activities on the reclamation process aboverequires considerable cost and its implementation should be planned so that the cost have to beeffective and efficient.Technical planning of reclamation on the outside dump Mahayung 2015 designed byrearranging the land by using the method of encapsulation, perform the promised land of tops toimmediately do revegetasi, make and take care of the channel that is in a outside dump ofMahayung to prevent erosion and maintain the water and add to the compartment on a pool ofMud and Precipitator liming regularly to prevent the occurrence of acid mine water. The cost forthe reclamation activities at the outside dump of Mahayung is the total cost of reclamationconsists of two that is direct costs and indirect costs. Direct costs for reclaiming the year 2015amount Rp 39.565.434.558,- and indirect costs Rp 3.758.716.283,- Then the total cost ofreclaiming the year 2015 amount to Rp 43.324.150.841